2018
DOI: 10.1111/jth.14224
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and the risk of incident pulmonary embolism in US women and men

Abstract: Background Moderate alcohol consumption has been variably associated with hemostatic and fibrinolytic factor levels, but the association between alcohol consumption and the risk of incident pulmonary embolism (PE) remains uncertain. Objective To evaluate alcohol consumption amount and frequency in relation to PE risk. Methods Nurses' Health Study (NHS), NHS II and Health Professionals Follow-Up Study participants free of venous thromboembolism (VTE) at baseline (n = 217 442) reported alcohol consumption by typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Two population-based studies from Denmark and studies of male American health care workers found no association between alcohol consumption and VTE in men. 14,[16][17][18] In two of these studies, exposure to alcohol was substantially higher than in our population, making comparison between our study and those studies difficult. 14,17 As shown in ►Supplementary Table S2 (available in the online version), placing teetotallers in a separate category did not change our results regarding the association between alcohol consumption and risk of VTE in men.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Two population-based studies from Denmark and studies of male American health care workers found no association between alcohol consumption and VTE in men. 14,[16][17][18] In two of these studies, exposure to alcohol was substantially higher than in our population, making comparison between our study and those studies difficult. 14,17 As shown in ►Supplementary Table S2 (available in the online version), placing teetotallers in a separate category did not change our results regarding the association between alcohol consumption and risk of VTE in men.…”
Section: Discussionmentioning
confidence: 95%
“…The prospective population-based American Atherosclerosis Risk in Communities study showed an association between alcohol intake and VTE, but the analysis was not stratified by sex. 10 Other prospective studies have not shown an association between alcohol intake and risk of VTE, 13,14 or have shown an inverse association in the elderly. 8 We found an association between alcohol consumption and VTE in men.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also noted a pattern of association between alcohol consumption and VTE similar to that reported in previous studies of alcohol consumption and nonfatal myocardial infarction. 32,37,38 (By contrast, alcohol consumption has previously been positively associated with risks of fatal coronary disease, stroke, and heart failure.) Although previous studies have reported that moderate alcohol consumption is associated with lower levels of hemostatic factors (eg, fibrinogen, factor VII, and von Willebrand factor), 39,40 further studies are needed to determine whether moderate alcohol consumption has a causal role in VTE.…”
Section: Discussionmentioning
confidence: 99%